2020
DOI: 10.3906/kim-2004-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg doping on morphology, photocatalytic activity and related biological properties of Zn1−xMgxO nanoparticles

Abstract: The objective of this study is to synthesize ZnO and Mg doped ZnO (Zn 1−x Mg x O) nanoparticles via the sol-gel method, and characterize their structures and to investigate their biological properties such as antibacterial activity and hemolytic potential.Nanoparticles (NPs) were synthesized by the sol-gel method using zinc acetate dihydrate (Zn(CH 3 COO) 2 .2H 2 O) and magnesium acetate tetrahydrate (Mg(CH 3 COO) 2 .4H 2 O) as precursors. Methanol and monoethanolamine were used as solvent and sol stabilizer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…In their study, Alev et al (2021) showed that copper doping increases density of point defects in ZnO structure and thus greatly enhances ethanol sensing properties of ZnO based nanorods. On the other hand, Yalcin et al (2020) showed that 2% magnesium doping into ZnO structure greatly inhibits hemolytic activity while leading an advanced antibacterial property. Since antibacterial property is mainly driven by interaction between incoming electromagnetic wave and catalytic material, determination of optical constants of catalytic materials is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Alev et al (2021) showed that copper doping increases density of point defects in ZnO structure and thus greatly enhances ethanol sensing properties of ZnO based nanorods. On the other hand, Yalcin et al (2020) showed that 2% magnesium doping into ZnO structure greatly inhibits hemolytic activity while leading an advanced antibacterial property. Since antibacterial property is mainly driven by interaction between incoming electromagnetic wave and catalytic material, determination of optical constants of catalytic materials is crucial.…”
Section: Introductionmentioning
confidence: 99%